Oxide dispersion strengthened copper and preparation method thereof

Through the combination of powder oxidation and cover rolling, the complex and cost-effectiveness of oxide diffusion-strengthening copper alloy is solved, and the uniform distribution and high performance of nano-oxides are achieved, and the mechanical properties and production efficiency of the material are improved.

CN119307766APending Publication Date: 2025-01-14JIANGXI COPPER TECHNOLOGY RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411325135.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing preparation methods of oxide dispersion-strengthening copper alloys have problems such as complex processes, long production cycles, high costs and uneven oxide distribution, which limits the further development and application of materials.

Method used

The combination of powder oxidation and powder cladding rolling technology is used to form CuO oxide films through low temperature oxidation in the air, and then cold rolling in the plastic cladding introduces defects and heat treatment at high temperatures to promote the formation and uniform distribution of nano oxides. Achieve effective combination of oxygen and active elements.

Benefits of technology

The uniform distribution and high performance of nano-oxide diffusion strengthening of copper is achieved, which reduces costs, improves the simplicity and efficiency of the process, avoids the problem of uneven distribution of oxides, and improves the mechanical properties of the alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307766A_ABST
    Figure CN119307766A_ABST
Patent Text Reader

Abstract

The invention relates to oxide dispersion strengthened copper and a preparation method thereof, and belongs to the technical field of metal composite materials. The preparation method of the oxide dispersion strengthened copper comprises the steps that atomized powder is oxidized in air to obtain oxygen-containing powder, the oxygen-containing powder is sealed in a sheath for cold rolling to introduce defects, then heat preservation is conducted at high temperature to promote formation of an oxide dispersion phase, and finally powder forming is achieved through multi-pass and low-deformation hot rolling. And thus, dispersion-strengthened copper with uniformly distributed dispersed phases is obtained. The introduction of oxygen elements can be conveniently and quickly realized through powder air oxidation, defects can be introduced in the cold rolling process to promote the diffusion of the oxygen elements and the formation of nano oxides, the preparation time can be greatly shortened through powder sheath hot rolling forming, the efficiency is improved, and possibility is provided for large-scale preparation of the oxide dispersion strengthened copper.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal composite materials, and in particular relates to oxide dispersion strengthened copper and a preparation method thereof. Background Art

[0002] Oxide dispersion strengthened copper alloy is a new type of composite material with excellent comprehensive physical and mechanical properties, and has both high strength and high conductivity and good resistance to high temperature softening. Among them, the dispersed phase particles are oxides with high melting point, good high temperature stability and high hardness. These oxide dispersed phase particles are evenly distributed in the copper matrix at the nanometer scale, and will not dissolve or coarsen at high temperatures close to the melting point of the copper matrix. Therefore, they can effectively hinder dislocation movement and grain boundary sliding, improve the room temperature and high temperature strength of the alloy, and at the same time do not significantly reduce the conductivity of the alloy.

[0003] Preparation methods of dispersion-strengthened copper alloys include internal oxidation, powder metallurgy, mechanical alloying, spray deposition and chemical precipitation, among which the internal oxidation method is relatively mature and widely used. However, the internal oxidation method has problems such as complex process, long production cycle, high cost and uneven oxide distribution, which limits the further development and application of dispersion-strengthened copper alloys.

[0004] Therefore, it is of great significance to develop a method for preparing oxide dispersion strengthened copper with a simpler process. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems existing in the above-mentioned prior art and provide a method for regulating the nano-oxide dispersed phase inside the alloy by combining powder oxidation with powder sheathing rolling technology, while ensuring the generation of nano-oxide dispersion strengthening phase, increasing the nucleation rate of the dispersed phase and making it uniformly distributed, thereby obtaining oxide dispersion strengthened copper with good performance and a preparation method thereof.

[0006] The present invention is achieved through the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing oxide dispersion strengthened copper, comprising the following steps:

[0008] (1) heating and oxidizing alloy powder to obtain oxidized powder; the alloy powder comprises at least one of Cu-Al alloy powder and Cu-Y alloy powder; the heating and oxidizing temperature is 200° C.-500° C.;

[0009] (2) placing the oxidized powder obtained in step (1) into a sheath, sealing, rolling, and heating and keeping warm; the sheath deformation during rolling is ≤30%;

[0010] (3) hot rolling the jacket after heat preservation in step (2) to obtain the oxide dispersion strengthened copper.

[0011] The present invention adopts a method combining powder air oxidation and powder sheath rolling to prepare oxide dispersion strengthened copper. The alloy powder is oxidized at low temperature in air to form an oxide film mainly composed of CuO on the powder surface; the powder is then placed in a sheath with good plasticity and sealed. The sealed sheath is rolled at room temperature to deform the powder. During this process, the oxide film on the powder surface is also deformed and broken. At the same time, a large number of defects such as dislocations and vacancies are introduced. These defects can promote the diffusion of oxygen elements into the powder and increase the nucleation rate of the oxide dispersed phase. Subsequently, the sheath is heated and kept warm at a relatively high temperature. The oxide film is decomposed during the heating process to provide oxygen for the formation of nano oxide dispersed phases, thereby achieving effective control of oxygen content, effective combination of oxygen with active elements Al and Y, and precipitation of nano composite oxides. At the same time, the powder can be formed in the process of low deformation and multiple passes of hot rolling. The obtained nano oxide dispersion strengthened copper has the advantages of uniform organization and uniform distribution of nano oxide dispersed phases.

[0012] Preferably, in step (1), the particle size of the alloy powder is ≤100 μm; more preferably, the particle size of the alloy powder is ≤50 μm.

[0013] Preferably, in step (1), the mass fraction of Al element or Y element in the alloy powder is less than 1%.

[0014] Preferably, in step (1), the alloy powder is obtained by melting alloy mother ingots in a vacuum induction furnace and atomizing and powdering.

[0015] Preferably, in the step (1), the heating oxidation is carried out in air.

[0016] Preferably, in step (1), the temperature of the heating oxidation is 200°C-350°C, and the time is 1h-10h.

[0017] Preferably, in step (1), the heating rate during the heating oxidation is not higher than 10°C / min; more preferably, the heating rate during the heating oxidation is not higher than 5°C / min.

[0018] The oxidation temperature in step (1) of the present invention is set at 200°C-500°C mainly to oxidize the alloy powder at a relatively slow rate, so that the oxygen content of the powder can be controlled by controlling the oxidation time. The oxidation time is determined according to the content of Al and Y to ensure that enough oxygen is introduced. If the oxidation temperature is too high, the powder may be severely oxidized in an instant, resulting in excessive oxygen content, which cannot be completely reduced later, seriously affecting the performance of the alloy. At the same time, controlling the oxidation temperature below 500°C is also to prevent Al and Y elements from segregating to the surface of the powder at high temperatures, thereby causing uneven distribution of nano-oxides and reducing the performance of the alloy. Furthermore, the heating rate during heating oxidation should not be too high. If the heating rate is too high, the powder on the surface will be rapidly oxidized to form a denser oxide film, thereby blocking the diffusion of oxygen in the air to the inside and affecting the oxidation inside the powder. The heating rate during heating oxidation is preferably not higher than 10°C / min, and more preferably not higher than 5°C / min.

[0019] Preferably, in step (2), the sheath comprises a stainless steel sheath, and the stainless steel sheath comprises any one of a 304 stainless steel sheath and a 316L stainless steel sheath.

[0020] Preferably, in step (2), the sealing is performed by welding.

[0021] Preferably, in step (2), the temperature during rolling is 25°C-35°C.

[0022] Preferably, in step (2), the sheath deformation during rolling is 20%-25%.

[0023] The rolling of the present invention can be carried out at room temperature (25°C-35°C). Cold rolling the sealed sheath can deform and break the powder as much as possible, introducing more defects. The deformation of the stainless steel sheath during cold rolling is ≤30%. Too high a deformation is likely to cause the sheath to crack, and too low a deformation cannot achieve the effect of deforming and breaking the powder. There are no special requirements for the pressure and time during rolling, as long as the sheath can be deformed.

[0024] Specifically, the sheath deformation is obtained by measuring the difference in block thickness before and after rolling, and dividing the difference by the thickness before rolling.

[0025] Preferably, in step (2), the temperature during the insulation is 800°C-1000°C; preferably, in step (2), the insulation time is 1h-3h.

[0026] The rolled sheath is heat treated to decompose CuO (CuO→Cu2O+O), and then O combines with Al and Y elements to form a nano-oxide dispersion phase. The Cu2O produced after the decomposition of CuO can also react with Al and Y at high temperatures to form an oxide dispersion phase. The heat treatment temperature and insulation time determine whether the nano-oxide phase can be generated and whether the oxide phase can aggregate and grow after generation. If the heat treatment temperature is too low, the oxide film on the surface of the oxide powder will not decompose and cannot provide oxygen for the generation of nano-oxides. If the temperature is too high, the oxide dispersion phase will aggregate and grow. Therefore, the preferred temperature for heating and insulation is 800°C-1000°C.

[0027] Preferably, in step (3), the hot rolling is performed multiple times, the temperature during the hot rolling is 800°C-1000°C, the deformation per pass is ≤15%, and the deformation of the jacket after hot rolling is ≥70%.

[0028] Specifically, the deformation of the sheath after hot rolling in the present invention is not less than 70% compared with the deformation before rolling in step (2), which can have a better forming effect, high density and good performance.

[0029] In a second aspect, the present invention provides oxide dispersion strengthened copper obtained by the preparation method of oxide dispersion strengthened copper.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) Different from the existing internal oxidation method, the present invention mainly generates CuO as a carrier of oxygen on the powder surface after oxidation, while in the prior art, oxygen is mainly introduced by adding Cu2O. The present invention introduces oxygen by oxidizing the alloy powder in the air, and then releases oxygen by decomposing CuO at high temperature, so as to promote the combination of Al and Y elements in the alloy with O to form a nano-oxide dispersion phase, thereby providing a low-cost method for the formation of an oxide dispersion-strengthened copper in-situ dispersion phase.

[0032] (2) A significant problem with the preparation of oxide-dispersed copper using only the method of air oxidation of powder is that the formed nano-oxide dispersion-strengthened phase is more likely to be concentrated near the original boundary of the powder and is unevenly distributed. The present invention uses a method that combines powder air oxidation and powder sheathing rolling. During the cold rolling process after the powder is loaded into the sheath, the oxidized powder will deform and break, thereby deforming and breaking the oxide film on the surface of the powder, achieving redistribution, avoiding the problem of the oxide being concentrated at the original boundary of the powder, and facilitating the uniform distribution of the oxide dispersion-strengthened phase. In addition, the nano-oxide strengthening phase is more likely to nucleate and grow at defects such as dislocations and vacancies. After the powder is loaded into the sheath and cold-rolled, a large number of defects such as dislocations and vacancies will be generated in the alloy. These defects have higher energy and can serve as oxide nucleation sites, which is conducive to the formation of more oxide dispersion-strengthened phases and improved alloy properties.

[0033] (3) Compared with other powder forming methods, such as hot isostatic pressing and hot extrusion, the powder encapsulation rolling process as a powder forming method has the characteristics of low cost and high efficiency. In addition, this method is not limited by the size of hot isostatic pressing or hot extrusion equipment, and can realize the preparation of large-sized nano-oxide dispersion-strengthened copper components. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is the surface morphology of the Cu-Al alloy powder after air oxidation treatment in step (1) of Example 1;

[0035] Figure 2 This is the metallographic diagram of the pressed billet obtained after rolling in step (2) of Example 1;

[0036] Figure 3 This is a SEM image of the oxide dispersion strengthened copper obtained in Example 1;

[0037] Figure 4 This is the metallographic image of the oxide dispersion strengthened copper obtained in Example 2;

[0038] Figure 5 This is a transmission electron microscope image of the oxide dispersion strengthened copper obtained in Example 2;

[0039] Figure 6 This is the SEM image of the oxide dispersion strengthened copper obtained in Comparative Example 1. DETAILED DESCRIPTION

[0040] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0041] Unless otherwise specified, the experimental methods used in the examples are all conventional methods; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels.

[0042] Example 1

[0043] A method for preparing oxide dispersion strengthened copper comprises the following steps:

[0044] (1) placing the alloy powder in a muffle furnace, heating the powder to 260° C. at a heating rate of 5° C. / min, and oxidizing at a constant temperature for 3 hours to obtain an oxidized powder; the alloy powder is Cu-0.6Al (mass percentage), and its preparation method is: using a 50 kg vacuum induction furnace to melt the alloy ingot, and then using argon spray powdering to obtain the above-mentioned Al-containing copper-based alloy powder, and screening out the powder with a particle size of less than 50 μm, so as to obtain the alloy powder;

[0045] (2) the oxidized powder obtained in step (1) is placed in a 304 stainless steel sheath, which is sealed by welding, and then the sheath is rolled at 25° C. with a deformation amount of 25%, and the deformed sheath is placed in a furnace at 900° C. and kept warm for 1 hour;

[0046] (3) hot rolling the copper sheet after heat preservation in step (2), with the hot rolling temperature at 900° C., the deformation amount per pass at 10%, and the final deformation amount of the copper sheet after hot rolling at 70%, thereby obtaining the oxide dispersion strengthened copper.

[0047] Figure 1 This is the surface morphology of the Cu-Al alloy powder after air oxidation treatment in step (1) of this embodiment. From the figure, we can see that after oxidation, the powder surface becomes rough and has a layer of oxide film. No large amount of oxide particles are observed, indicating that a large amount of stable Al2O3 will not be generated on the powder surface during low-temperature oxidation. Figure 2 This is the metallographic phase of the pressed billet obtained after rolling in step (2) of this embodiment. Figure 2 It can be seen that the original powder is deformed during the rolling process, and the oxide film is also deformed and broken, and the distribution in the compact is more uniform, which is conducive to the formation of nano-oxides. Figure 3 This is the SEM image of the oxide dispersion strengthened copper obtained in this example. Figure 3 It can be seen that a large amount of oxide dispersion strengthening phase is generated inside the alloy, indicating that the preparation method of oxide dispersion strengthening copper of the present invention can effectively promote the formation of in-situ dispersion phase and make its distribution more uniform. The room temperature tensile strength of the obtained dispersion strengthening copper sample is 533Mpa, which has good mechanical properties.

[0048] Example 2

[0049] A method for preparing oxide dispersion strengthened copper comprises the following steps:

[0050] (1) placing the alloy powder in a muffle furnace, heating the powder to 300° C. at a heating rate of 5° C. / min, and oxidizing at a constant temperature for 1 hour to obtain an oxidized powder; the alloy powder is Cu-0.19Al (mass percentage), and its preparation method is: using a 100 kg vacuum induction furnace to melt the alloy ingot, water atomizing powder to obtain the above-mentioned Al-containing copper-based alloy powder, and screening out the powder with a particle size of less than 50 μm to obtain the alloy powder;

[0051] (2) the oxidized powder obtained in step (1) is placed in a 304 stainless steel sheath, which is sealed by welding, and then the sheath is rolled at 25° C. with a deformation amount of 20%, and the deformed sheath is placed in a furnace at 950° C. and kept warm for 1 hour;

[0052] (3) hot rolling the copper sheet after heat preservation in step (2), with the hot rolling temperature at 950° C., the deformation amount per pass at 10%, and the final deformation amount of the copper sheet after hot rolling at 75%, thereby obtaining the oxide dispersion strengthened copper.

[0053] Figure 4 This is a metallographic picture of the oxide dispersion strengthened copper alloy obtained in this example. The alloy ingot has good density and no obvious cracks. Figure 5 This is a transmission electron microscope image of the oxide dispersion-strengthened copper alloy of this embodiment. In the image, it can be observed that a large number of 10nm-30nm dispersion-strengthened phases are generated and evenly distributed, which shows that the method of combining air oxidation and powder sheathing rolling molding in the present invention can promote the formation of in-situ dispersion phases of dispersion-strengthened copper and regulate its distribution state to make it evenly distributed. The room temperature tensile strength of the obtained dispersion-strengthened copper sample is 350Mpa.

[0054] Example 3

[0055] The preparation method of oxide dispersion strengthened copper in this embodiment is different from that in embodiment 1 in that the temperature of heating oxidation in step (1) is 350° C., and the other preparation parameters are the same as those in embodiment 1, to obtain oxide dispersion strengthened copper in this embodiment. The size and density of the precipitated phase inside the oxide dispersion strengthened copper in this embodiment are close to those in embodiment 1, and the room temperature tensile strength is 528 Mpa.

[0056] Example 4

[0057] The preparation method of oxide dispersion strengthened copper in this embodiment is different from that in embodiment 1 in that the temperature of heating oxidation in step (1) is 500° C., and the other preparation parameters are the same as those in embodiment 1, to obtain oxide dispersion strengthened copper in this embodiment. Compared with embodiment 1, the oxide dispersion strengthened copper in this embodiment has more large-particle aluminum oxide precipitates generated inside, and the tensile strength of the alloy is 503 MPa.

[0058] Example 5

[0059] The preparation method of oxide dispersion strengthened copper in this embodiment is different from that in embodiment 1 in that the sheath deformation during rolling in step (2) is 30%, and the other preparation parameters are the same as those in embodiment 1, to obtain oxide dispersion strengthened copper in this embodiment. The mechanical properties and microstructure of the oxide dispersion strengthened copper in this embodiment are similar to those of the sample in embodiment 1, but due to the high sheath deformation, the sheath is easily broken during rolling, and the success rate of sample preparation is reduced.

[0060] Example 6

[0061] The preparation method of oxide dispersion strengthened copper in this embodiment is different from that in embodiment 1 in that the sheath during rolling in step (2) is a 45 steel sheath. During rolling, the 45 steel sheath has insufficient plasticity and is very easy to break, resulting in powder outflow, and the final forming of the powder cannot be guaranteed.

[0062] Comparative Example 1

[0063] A method for preparing oxide dispersion strengthened copper comprises the following steps:

[0064] (1) placing the alloy powder in a muffle furnace, heating the powder to 260° C. at a heating rate of 5° C. / min, and oxidizing at a constant temperature for 3 hours to obtain an oxidized powder; the alloy powder is Cu-0.6Al (mass percentage), and its preparation method is: using a 50 kg vacuum induction furnace to melt the alloy ingot, and then using argon spray powdering to obtain the above-mentioned Al-containing copper-based alloy powder, and screening out the powder with a particle size of less than 50 μm, so as to obtain the alloy powder;

[0065] (2) The oxidized powder obtained in step (1) is placed in a stainless steel sheath and cold pressed at a temperature of 25° C., a pressure of 500 MPa, and a time of 180 seconds. The formed sheath is placed in a furnace at 900° C. and kept warm for 1 hour to obtain the oxide dispersion strengthened copper.

[0066] Figure 6 The SEM image of the oxide dispersion strengthened copper obtained in this comparative example is as follows: Figure 6 It can be clearly seen that the oxide particles are concentrated near the original boundary of the powder, the oxide dispersed phase is severely unevenly distributed, and the tensile strength at room temperature is only 368Mpa.

[0067] Comparative Example 2

[0068] The preparation method of the oxide dispersion-strengthened copper in this comparative example is different from that in Example 1 in that the temperature of the heating oxidation in step (1) is 600° C., and the other preparation parameters are the same as those in Example 1, to obtain the oxide dispersion-strengthened copper in this comparative example. The oxide dispersion-strengthened copper in this comparative example is oxidized by air at too high a temperature, and the powder surface is rapidly oxidized to form a dense oxide film, which prevents oxygen in the air from entering the interior of the powder. The final sample is insufficient in oxygen, and the amount of the generated dispersion-strengthened phase is small, and the tensile strength at room temperature is only 400 MPa.

[0069] Comparative Example 3

[0070] The preparation method of oxide dispersion strengthened copper in this comparative example is different from that in Example 1 in that the sheath deformation during rolling in step (2) is 35%. Since the sheath deformation during rolling is too large, the sheath is prone to cracking after cold rolling, resulting in the outflow of powder inside the sheath, making it impossible to carry out the subsequent hot rolling forming process, and the success rate of sample preparation is low.

[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing oxide dispersion strengthened copper, characterized in that: The following steps are involved: (1) heating and oxidizing alloy powder to obtain oxidized powder; the alloy powder comprises at least one of Cu-Al alloy powder and Cu-Y alloy powder; the heating and oxidizing temperature is 200° C.-500° C.; (2) placing the oxidized powder obtained in step (1) into a sheath, sealing, rolling, and heating and keeping warm; the sheath deformation during rolling is ≤30%; (3) hot rolling the jacket after heat preservation in step (2) to obtain the oxide dispersion strengthened copper.

2. The method for preparing oxide dispersion strengthened copper according to claim 1, characterized in that: In the step (1), the particle size of the alloy powder is ≤100 μm; and / or the mass fraction of the Al element or the Y element in the alloy powder is <1%.

3. The method for preparing oxide dispersion strengthened copper according to claim 1, characterized in that: In the step (1), the temperature of the heating oxidation is 200°C-350°C, and the time is 1h-10h.

4. The method for preparing oxide dispersion strengthened copper according to claim 1, characterized in that: In the step (1), the heating rate during the heating oxidation is not higher than 10°C / min.

5. The method for preparing oxide dispersion strengthened copper according to claim 1, characterized in that: In the step (2), the sheath comprises a stainless steel sheath.

6. The method for preparing oxide dispersion strengthened copper according to claim 1, characterized in that: In the step (2), the sheath deformation during rolling is 20%-25%.

7. The method for preparing oxide dispersion strengthened copper according to claim 1, characterized in that: In the step (2), the temperature during the insulation is 800°C-1000°C.

8. The method for preparing oxide dispersion strengthened copper according to claim 1, characterized in that: In the step (3), the temperature during hot rolling is 800°C-1000°C, the deformation per pass is ≤15%, and the deformation of the jacket after hot rolling is ≥70%.

9. The method for preparing oxide dispersion strengthened copper according to claim 1, characterized in that: Satisfy at least one of the following: (1) In step (1), the heating oxidation is carried out in air; (2) In step (1), the heating rate during the heating oxidation is not higher than 5°C / min; (3) In step (2), the temperature during rolling is 25°C-35°C; (4) In step (2), the insulation time is 1 h to 3 h.

10. Oxide dispersion strengthened copper obtained by the method for preparing oxide dispersion strengthened copper according to any one of claims 1 to 9.